Scale up the collection area of luminescent solar concentrators towards metre-length flexible waveguiding photovoltaics - Correia, Sandra F. H.; Lima, Patrícia P.; Pecoraro, Edison [UNESP]; Ribeiro, Sidney J. L. [UNESP]; André, Paulo S.; Ferreira, Rute A. S.; Carlos, Luís D. (Wiley, 2016)
Luminescent solar concentrators (LSCs) are cost-effective components easily integrated in photovoltaics (PV) that can enhance solar cells' performance and promote the integration of PV architectural elements into buildings, with unprecedented possibilities for energy harvesting in façade design, urban furnishings and wearable fabrics. The devices' performance is dominated by the concentration factor (F), which is higher in cylindrical LSCs compared with planar ones (with equivalent collection area and volume). The feasibility of fabricating long-length LSCs has been essentially limited up to ten of centimetres with F < 1. We use a drawing optical fibre facility to easily scale up large-area LSCs (length up to 2.5 m) based on bulk and hollow-core plastic optical fibres (POFs). The active layers used to coat the bulk fibres or fill the hollow-core ones are Rhodamine 6G- or Eu3+-doped organic–inorganic hybrids. For bulk-coated LSCs, light propagation occurs essentially at the POFs, whereas for hollow-core device light is also guided within the hybrid. The lower POFs' attenuation (~0.1 m−1) enables light propagation in the total fibre length (2.5 m) for bulk-coated LSCs with maximum optical conversion efficiency (ηopt) and F of 0.6% and 6.5, respectively. For hollow-core LSCs, light propagation is confined to shorter distances (6–9 × 10−2m) because of the hybrids' attenuation (1–15 m−1). The hollow-core optimised device displays ηopt= 72.4% and F = 12.3. The F values are larger than the best ones reported in the literature for large-area LSCs (F = 4.4), illustrating the potential of this approach for the development of lightweight flexible high-performance waveguiding PV. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: lanthanide ions; luminescent solar concentrators; metre-length; organic dyes; organic–inorganic hybrids; plastic optical fibres